Le féminisme pris aux pièges - Gail Pheterson (Genre, Sexualité et Société)
This article sketches the distancing of dominant feminist orientations from the struggle against institutional and ideological sexism, most notably in their collusion with governments to « protect » women against criminal violence, and in their abandon of coalitions between women in the hope of gaining rights as a sexual minority. In the early 1980’s, intense debates ensued between so-called anti-violence/anti-prostitution and pro-rights/pro-sex feminists. Those who championed the cause of sexually transgressive women were identified as sex radicals. Over the past thirty years, anti-violence feminists have succeeded in mainstreaming their objectives in national legislative reforms, NGOs, UN conventions and popular media. Some sex radical feminists, worn down by the complicity of anti-violence crusaders with governments in search of ideological credit to justify discriminatory control of undocumented migrants and illicit revenues, have found a less antagonistic political base in a Lesbian, Gay, Bi-sexual, Transgender alliance. This erosion of feminist coalitions, however conflictive they may be, represents a decentering – or erasure – of radical feminism in favour of protectionist reforms, on one side, and integrationist reforms, on the other.